2010
DOI: 10.5851/kosfa.2010.30.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tannery Wastes on the Fattening of Growing Cattle, Carcass, and Meat Quality

Abstract: The present study was conducted to determine the effect of tannery waste protein concentrate (TWPC) on fattening of cattle and the carcass and meat quality, with the aim of replacing the costly commercial protein concentrate (Jasoprot) with a more economical and effective alternative. Twelve young cattle (six male and six female) were fed during the study period on a control diet (T1) with 10% Jasoprot and on two test diets: 5% TWPC + 5% Jasoprot (T2) and 10% TWPC (T3). The test diets significantly affected (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Organoleptic scores remained consistent across diets, suggesting no compromise in meat quality. Thus, combined with Jasoprot, tannery waste protein concentrate emerged as a cost-effective substitute in the cattle industry without affecting meat or carcass quality [132,133].…”
Section: Evaluation Of Security Of Recycled Solid Chromed Tannery Was...mentioning
confidence: 99%
See 1 more Smart Citation
“…Organoleptic scores remained consistent across diets, suggesting no compromise in meat quality. Thus, combined with Jasoprot, tannery waste protein concentrate emerged as a cost-effective substitute in the cattle industry without affecting meat or carcass quality [132,133].…”
Section: Evaluation Of Security Of Recycled Solid Chromed Tannery Was...mentioning
confidence: 99%
“…The predominant concern with chromed tannery wastes lies in the high chromium levels in extracted collagen, potentially endangering humans eating such meat. While studies by Silva et al [130], Jini et al [131], Jahangir-Alam et al [133], and Zhao et al [126] saw no issues with tannery wastes, five other researchers identified chromed wastes as dietary risks for animals. This emphasizes the need for effective dechroming before using tannery residues in animal feeds.…”
Section: Evaluation Of Security Of Recycled Solid Chromed Tannery Was...mentioning
confidence: 99%
“…Some authors have studied the influence of vegetabletanned wastes on the diet of broilers [142] and cattle [143]. In both studies three distinct diets were tested: D1 (containing 10% commercial protein concentrate), D2 (containing 5% commercial protein concentrate + 5% tannery waste) and D3 (containing 10% tannery waste).…”
Section: Animal Dietmentioning
confidence: 99%
“…The by-products and wastes of slaughterhouse and chickens are perishable, but the processing of waste as alternative protein concentrate as commercial protein concentrate can be of good quality and it could be preserved for a long time and become very useful over time. Protein concentrate from tannery wastes described by [9] is helpful for the preparation of waste protein concentrate but it was not used. Processing of fleshing meal is similar to the preparation of waste protein concentrate as described by [7].…”
Section: Preparation Of Alternative Protein Concentratesmentioning
confidence: 99%